Pelatihan personal grooming dan hygiene dalam dunia kerja - Ira B Hubner; Juliana Juliana; Amelda Pramezwary; Wilhelmina Rosse Marisca Gajeng (Abdimas Siliwangi, 2022)
Community Service is one of the Tri Dharma Higher Education activities organized by the Faculty of Tourism, Pelita Harapan University. From the PkM held, it is hoped that both lecturers and students can share the knowledge they get in higher education with the community, and bring benefits to the community in carrying out their daily lives. The PkM implementation this time aims to provide knowledge and information about grooming and hygiene so that the general public can find out how to look neat and clean so they can enter the world of work more professionally, especially in the hospitality industry. In the world of hospitality, grooming and hygiene standards are the most important things to serve guests. Emmanuel Foundation's targeted partners have training needs for students currently in high school. It is hoped that the training can prepare students to be more confident in entering the world of work, especially in the world of hospitality. Activities are carried out online via zoom with Knowledge material about the importance of Personal Grooming and Hygiene at work. Aspects in Personal Grooming and Hygiene Application of Basic Grooming and Hygiene. The activities carried out are expected to continue to develop and apply the materials and training provided in implementing Personal Grooming and Personal Hygiene in the world of work.